2019
DOI: 10.1002/ange.201901059
|View full text |Cite
|
Sign up to set email alerts
|

Formation of Glyoxylic Acid in Interstellar Ices: A Key Entry Point for Prebiotic Chemistry

Abstract: With nearly 200 molecules detected in interstellar and circumstellar environments,t he identification of the biologically relevant a-keto carboxylic acid, glyoxylic acid (HCOCOOH), is still elusive.H erein, the formation of glyoxylic acid via cosmic-ray driven, non-equilibrium chemistry in polar interstellar ices of carbon monoxide (CO) and water (H 2 O) at 5K via barrierless recombination of formyl (HCO) and hydroxycarbonyl radicals (HOCO) is reported. In temperature-programmed desorption experiments,the subl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 55 publications
(30 reference statements)
0
2
0
Order By: Relevance
“…[20][21][22] In general, hydroxycarbenes undergo barrierless carbonyl ene reactions with carbonyl compounds in the gas phase, yielding biorelevant molecules, including the carbohydrates glycolaldehyde and glyceraldehyde. 23 Eckhardt et al 24 and Turner et al 25,26 recently demonstrated the formation of glyoxylic acid (HC(O)COOH) and even (di)phosphates (PO 4 3À /P 2 O 7 4À ) in ices modeling interstellar conditions, providing compelling evidence that essential biorelevant molecules, together with their precursors, might form in deep space. At least a fraction of these abiotically synthesized compounds might be incorporated into meteoritic parent bodies and could have survived successive meteorite or comet impact on the Earth, thus reinforcing the theory of an exogenous source of key prebiotic molecules on the Earth.…”
Section: Introductionmentioning
confidence: 99%
“…[20][21][22] In general, hydroxycarbenes undergo barrierless carbonyl ene reactions with carbonyl compounds in the gas phase, yielding biorelevant molecules, including the carbohydrates glycolaldehyde and glyceraldehyde. 23 Eckhardt et al 24 and Turner et al 25,26 recently demonstrated the formation of glyoxylic acid (HC(O)COOH) and even (di)phosphates (PO 4 3À /P 2 O 7 4À ) in ices modeling interstellar conditions, providing compelling evidence that essential biorelevant molecules, together with their precursors, might form in deep space. At least a fraction of these abiotically synthesized compounds might be incorporated into meteoritic parent bodies and could have survived successive meteorite or comet impact on the Earth, thus reinforcing the theory of an exogenous source of key prebiotic molecules on the Earth.…”
Section: Introductionmentioning
confidence: 99%
“…For understanding how the emergence of metabolism could have occurred in a geological environment, much work focuses on studying reactions of organic molecules that are both important to modern biology and also are likely to have been present at life's origin. Pyruvate and glyoxylate are two carboxylic acid compounds that are of particular prebiotic interest: They are central to modern biochemistry, can be synthetized abiotically (Cody et al., 2000; Echkardt et al., 2019; Eggins et al., 1988; Marín‐Yaseli et al., 2016; Mohammed et al., 2017; Varma et al., 2018), and can lead into a variety of important reaction pathways for origin of life including reactions that resemble ancient proto‐metabolic cycles (Muchowska et al., 2017, 2019). In previous studies, pyruvate and/or glyoxylate have been shown to react with redox‐active iron minerals and/or dissolved Fe 2+ and various nitrogen sources to form amino acids, alpha‐hydroxy acids (αHA's), thiols, and other citric acid cycle intermediates (Barge et al., 2019; Huber & Wächtershäuser, 2003; Muchowska et al., 2017, 2019; Novikov & Copley, 2013).…”
Section: Introductionmentioning
confidence: 99%